Digital capital and food agricultural SMEs: Examining the effects on SME performance, inequalities and government role - Fanny Saruchera; Sinenhlanhla Mpunzi (Cogent Business & Management)
This paper provides an explorative and interrogative profile of digital capital on SMEs within the agricultural food sector, focusing on SME farmers. Digital capital is deemed the new capital essential for farmers. The paper examines the opportunities and threats offered by digital capital and explores how it influences agricultural SME performance and how it leads to digital inequalities. The study purposively sampled three South African agricultural provinces and adopted a purposive sampling technique to collect quantitative and qualitative data. With the undoubted contribution of SMEs to social and economic fronts, the study chronicled how digital capital has improved the value chain processes while unearthing the barriers to digital tools access. It emerged that SMEs face many adoption challenges; hence it is debatable to link positive SME performance to digital capital adoption. It emerged that agricultural SMEs mostly adopt complimentary service digital tools, indicating that digital capital is a catalyst for inequalities. While the government has implemented some initiatives to promote digital capital adoption, such interventions remain inadequate. The study contemplates other initiatives that could be adopted to address the barriers SMEs face in this digital era, hence closing the inequalities gap within the industry. SMEs should be subject to public policy support and protection, particularly on digital capital incentives and sponsorship. The government must regulate some digital capital tools which are more harmful than productive.